New genus and species of apterous Carventinae from Costa Rica and Grenada (Hemiptera, Heteroptera, Aradidae) - Heiss, Ernst (Zootaxa, 2021)
Only three species assigned to two genera of the flat bug subfamily Carventinae Usinger, 1950 are recorded to date from Costa Rica and one genus and species from Grenada. Following apterous carventine taxa are described and illustrated in the present paper: Joceliaptera graziae gen. et sp. nov.; Peggicoris cahuitanus sp. nov.; Peggicoris grenadensis sp. nov. Joceliaptera gen. nov. is compared with most similar Neotropical genera. A key to species of Peggicoris is presented.